Balancing the pressures: a review of the quality of care provided to children and young people aged 0–24 years who were receiving long-term ventilation. (2nd September 2020) - Freeth, Heather; Mahoney, Nicholas; Juniper, Mark; Moses, Rachael; Wilkinson, Kathy
Abstract : Assessing the quality of care for patients receiving long-term ventilation is complex given the diversity of this population (0–24 years in this case) and their differing requirements for treatment. This article details how and why such reviews are necessary.